Liberated through teddy bears: resistance, resourcefulness, and resilience in toy play during the COVID-19 pandemic - Heljakka Katriina (Taylor & Francis, 2022)
As a result of the global COVID-19 pandemic, Finnish citizens started to display teddy bears in their windows. As this activity gained media interest and popularity, it grew into a transgenerational form of toy play, where children and adults participated as displayers and spectators in this visual-material play pattern, made available to a broader audience through sharing on social media. A previous phase of the study articulated and analyzed the phenomenon as an act that facilitates mental well-being through imagination, participation, and playing for the common good (Heljakka, 2020). By theorizing and framing the phenomenon as pandemic toy play, the researcher suggested the importance of resistance, resourcefulness, and playful resilience in times of forced self-isolation and social distancing. This article builds on the earlier phase of the study by focusing on the previously identified themes and investigates the occurrence of these themes in adult toy play during a pandemic.